A Refusal of State-Driven Northern Destiny: Deconstructing the Mackenzie Valley Pipeline Inquiry Hearings - Ozbilge, Nevcihan (2022)
This dissertation considers the incommensurable interests of people, fossil capital, federal energy politics, and place in Northern Canada during the 1970s. By the late 1960s, the insatiable North American appetite for fossil fuels had turned its attention toward the Arctic region. After the discovery of rich deposits in Prudhoe Bay, Alaska, in 1968, largescale energy projects were proposed to access and exploit these Arctic natural resources. Canada participated in this northern oil rush; an exploration of oil and gas in the Arctic regions was accelerated in the early 1970s. The next challenge involved transporting the oil and gas to southern markets. In 1974, the Canadian federal government initiated the Mackenzie Valley Pipeline Inquiry to investigate the social, environmental, and economic effects of the pipeline routes proposed by a consortium of American and Canadian oil companies through the Mackenzie River Valley in the Northwest Territories where it would connect with existing pipeline infrastructure in northern Alberta. The Inquiry’s report recommended against immediate construction, encouraging instead a ten-year moratorium. Inquiry commissioner Thomas Berger’s report rationalized the delay to make time for settling Indigenous land claims in the region and for taking conservation measures to protect some key areas in the Mackenzie River Valley. In this dissertation, I examine how the discussion around pipeline construction shaped the meaning of the North, self-determination, and cultural recognition. In this dissertation, I particularly focus on how Indigenous peoples asserted their claims by rejecting state-driven policies and the interests of fossil-fuel capitalism in the North. Thesis Doctor of Philosophy (PhD) Through the close reading of the Mackenzie Valley Pipeline Inquiry hearings, I examine how the discussion around energy development shaped the 1970s’ contentious Canadian politics of nation and North. Central to this debate, I focus on how Indigenous peoples asserted their land claims ...